A new grass frog with rupicolous tadpoles from northern Zambia (Anura: Ptychadenidae) - Channing, Alan; Willems, Frank (Zootaxa, 2018)
We describe a new species of Ptychadena from Mutinondo Wilderness in northern Zambia. It has rupicolous tadpoles that develop in a film of water. The species is distinguished on morphology, advertisement call and DNA sequences from other grass frogs and was found to be most closely related to P. broadleyi. It has no contrasting longitudinal bands on the posterior thigh, the foot is longer than half SVL, it has no light triangle on the snout, three phalanges of the fourth toe free of web and the snout has no skin folds. The species should be considered Near Threatened in terms of the IUCN Red List criteria given its limited extent of occurrence and population size.